Biopsychosocial Factors, Life Course Perspective, and Their Influences on Language Development in Children - Safriana, Latifah; Salimo, Harsono; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2017)
Background: Speech and language disorder if untreated may cause deficiency in reading, verbal, psychosocial, behavioral, and academic abilities. Studies have shown that birthweight, body length at birth, maternal education, parenting style, maternal stress, income at pregnancy, and current income can influence child development. This study aimed to determine the biopsychosocial factors, life course perspective, and their influences on language development in children. Subject and Method: This was an analytic observational study using case control design. The study was conducted in Surakarta, Central Java, from February to May 2017. A sample of 140 children aged 2 to 5 years old were selected for this study by fixed disease sampling with 1:3 ratio between case (children with speech and language disorder) and control (children without such disorder). The dependent variable was child speech and language development. The independent variables were birthweight, body length at birth, maternal education, maternal stress, parenting style, family income at pregnancy, and current family income. The data were collected by a set of questionnaire and medical record. The data on speech and language ability was measured by Denver II questionnaire. Path analysis was employed for data analysis.Results: Language development was directly and positively affected by democratic parenting style (b=0.46; SE=0.08; p<0.001), permissive parenting style (b=0.10; SE=0.11; p=0.020), birthweight (b=0.12; SE=0.02; p=0.002), maternal education (b=0.11; SE=0.31; p=0.007), maternal stress (b=-0.13; SE=0.04; p=0.013). Language development directly and negatively affected by autoritarian parenting style (b=-0.37; SE=0.09; p<0.001). Language development was indirectly affected by body length at birth, family income at pregnancy, and current family income.Conclusion: Language development is directly affected by parenting style, birthweight, maternal education, maternal stress.Keywords: biopsychosocial, life course, language development, children 2 to 5 years old, path analysisCorrespondence:ÃÂ Latifah Safriana. School of Health Polytechnics Permata Indonesia, Yogyakarta. Email: latifsafri@gmail.com. Mobile : +6282225246917.Journal of Maternal and Child Health (2017), 2(3): 245-256https://doi.org/10.26911/thejmch.2017.02.03.06